The total ozone amount changes over Lithuania and neighbouring countries - Tretjakovas, Sergejus; Girgždys, Aloyzas; Masilevičius, Rolandas (Journal of Environmental Engineering and Landscape Management, 2012)
Changes in the total ozone amount (TOA) above Lithuania and neighbouring countries during the period 1993–2008 have been analysed. The present study focuses on the TOA seasonal variations over the aforementioned area. The statistical data of measurements were analysed. The detailed information of TOA was presented by the Lithuanian Hydrometeorological Service and the World Ozone and Ultraviolet Radiation Data Centre (WOUDC). The net of stations measuring the TOA changes was set; it consisted of 16 meteorological stations. The coefficients of correlation of TOA changes between various stations were calculated basing upon the Pearson’s Correlation Coefficient. It was established that the seasonal TOA variation tendencies were coincident between the stations and most linear correlation coefficients between Lithuania and neighbouring countries were 0.9 and 1.0. During the analysis of TOA data, it was established that the results of measurements performed in Lithuania from May 1999 to February 2000 and from May 2000 to January 2001 were insufficiently precise. To estimate TOA in Lithuania (at Kaunas Meteorological Station) without performing direct measurements, the linear function was calculated using the least squares method and the data obtained from the investigated net of meteorological stations. The difference between calculated and measured TOA results was up to 8%. Article in English. Bendrojo ozono kiekio pokyčiai virš Lietuvos ir kaimyninių šalių Santrauka. Remiantis 1993–2008 m. duomenimis, nagrinėjami bendrojo ozono kiekio (BOK) pokyčiai virš Lietuvos ir kaimyninių šalių. Įvertintos sezoninių šių BOK pokyčių sąsajos. Išsamiõs informacijos apie BOK pateikė Lietuvos hidrometeorologijos tarnyba bei Pasaulio ozono ir ultravioletinės spinduliuotės duomenų centras. Sudarytas bendrojo ozono kiekio matavimo stočių tinklas iš 16 meteorologinių stočių. Analizuojant BOK pokyčių tarp skirtingų stočių tiesinės sąsajos stiprumą taikyti Pirsono koreliacijos koeficientai. Nustatyta, kad BOK sezoninių pokyčių tendencijos tarp šių stočių sutampa, ir dauguma koreliacijos koeficientų (tarp Lietuvos ir kaimyninių šalių) yra 0,9–1,0. Analizuojant BOK duomenis, nustatyta, kad nuo 1999 m. gegužės iki 2000 m. vasario ir nuo 2000 m. gegužės iki 2001 m. sausio Lietuvoje atliktų matavimų rezultatai nėra pakankamai tikslūs. Mažiausiųjų kvadratų metodu apskaičiuota tiesinė funkcija BOK nustatyti Lietuvoje (Kauno meteorologijos stotyje) neatliekant tiesioginių matavimų. BOK skaičiavimo ir matavimo rezultatų skirtumas siekia iki 8%. Reikšminiai žodžiai: bendrasis ozono kiekis, meteorologijos stotis, tiesinės koreliacijos koeficientai, stebėsena